Isolasi Senyawa Metabolit Sekunder Dari Ekstrak Heksana Batang Kelakai (Stenochlaena palustris): - Pardede, Antoni; Wardhani, Rr. Ariessanty Alicia Kusuma (Universitas Andalas, 2024)
Isolation is a method of obtaining pure secondary metabolite compounds from plant extracts, which provide benefits such as health, medicine, cosmetics, and agriculture. This research has been carried out and aims to isolate the secondary metabolite compound from the hexane extract of the kelakai stems (Stenochlaena palustris). Phytochemical screening of that extract resulted in a positive-containing steroid. The isolation method includes the separation of hexane extract with column chromatography using silica gel as the stationary phase and eluted successively with hexane, chloroform, and ethyl acetate (step gradient polarity). The column chromatography of the hexane extract resulted in five fractions (H1–H5). Furthermore, fraction H3 was purified to obtain a white needle crystal. The isolated compound spot is invisible in thin-layer chromatography (KLT) under an ultraviolet lamp at 254 nm and 365 nm wavelengths. The isolated compound structure was elucidated by proton and carbon nuclear magnetic resonance (NMR), and mass spectroscopy (MS), as well as comparisons with literature data. The isolated compound is a group of steroids identified as β-sitosterol with the molecular formula C29H50O.